Appraisal Attitude Analysis of Debate Verbal Adjudication - Tarigan, Desmery Natalia; Zein, T. Thyrhaya; Harefa, Yulianus (LingPoet: Journal of Linguistics and Literary Research, 2022)
This research investigates the appraisal attitudinal framework to identify the level of attitude (affect, judgment, and appreciation) in debate verbal adjudication conducted through descriptive qualitative method. The theories supporting this thesis are the ones proposed by Martin & White, Halliday, and Austin J. Freeley. The primary data sources in this thesis were five verbal adjudications of debate adjudicators from preliminary rounds of AEO 2020. The data in this study were lexical resources and phrases for appraisal attitudinal framework. The steps passed in this analysis are collecting the data by transcribing the recorded debate verbal adjudication into text, identifying the lexical resources and phrases, and concluding the analysis. The result of this thesis shows the score obtained for appraisal attitude resources in five debate verbal adjudications. The results present that the Appreciation score obtained was 59.1% in average, Judgment score obtained was 33.2% in average, and Affect score obtained was 7.7% in average. Thus, the level of appraisal attitudinal framework in debate verbal adjudications account for higher attitude of language evaluation. It is also demonstrates that the appraisal attitudinal element plays pivotal role in terms of directing evaluation towards the debater’s performance